Strategies to prevent and reduce gambling harm in Australian women. (4th March 2023) - McCarthy, Simone; Pitt, Hannah; Bellringer, Maria E.; Thomas, Samantha L.
Abstract: There are increasing global concerns about women's participation in gambling, and their risk of gambling-related harm. Limited attention has been given to the range of specific and tailored strategies that may be used to prevent and reduce women's risk of gambling-related harm. This study aimed to understand how key informants in Australia conceptualised the risks facing women who gamble, and the range of tailored strategies that could be used to respond. Online focus groups were conducted with n  = 15 key informants working in gambling research, policy, prevention, treatment services, and five women with lived experience of gambling harm (as Experts by Experience). A reflexive approach to thematic analysis was used to guide the data interpretation. Gambling harm was recognised as a hidden problem for women. There were a number of knowledge gaps that key informants acknowledged they had about women, with participants suggesting that older rather than younger women were most at risk of experiencing gambling harm. Participants recommended a range of de-normalisation strategies that could specifically target women – including strategies to address the barriers for women attending recreational and social alternatives, co-producing public health messages with women for public education initiatives, and providing anonymous pathways for women to participate in advocacy for gambling reform.